Translating the Connotations of Allah's 'Makr' in the Noble Quran - الطاهر، محمد أنور (الجامعة الأردنية - عمادة البحث العلمي, 2021)
تبحث هذه الدراسة في الأخطاء المتعلقة بترجمة المعاني الإيحائية للفظة (المكرر) في القرآن الكريم. فهذه اللفظة يغلب عليها المعني السلبي في اللغة العربية المعاصرة، ولكنها تنسب إلي الله تعالي في ستة مواضع، فيفهمها بعض الناطقين بغير العربية على معني التآمر أو الخداع، فتأتي الدراسة على عدة عوامل تتعلق بهذه القضية، مثل التطور الدلالي، ووصف الله – سبحانه وتعالي-في القرآن الكريم، وسياق الكلام، وأسلوب المشاكلة-وهو أهم هذه العوامل. وبعد ذلك تنظر في المعاني التفصيلية التي يذكرها القاموس لخيارات عشرة من المترجمين بهدف معرفة الأفضل منها من ناحية المعاني الإيحائية.
The present study explores the mistranslation of the original connotations of ‘Makr’ in the Noble Quran. Although it currently tends to carry a negative sense, the word is connected to Almighty Allah in six verses and misinterpreted by some non-native speakers of Arabic as plotting or, even, deception. Therefore, several relevant factors are investigated, such as semantic change, the attributes of Allah in the Noble Quran, the contextual meaning and, most importantly, the Arabic style of Mushakala. Finally, choices by ten translators are subject to dictionary analysis to guide to those with the appropriate connotations.
Keywords: القرآن الكريم -- تفسير القرآن -- ألفاظ القرآن -- دلالات مكر الله